the Dynamics Of Exchange Rate Volatility In Indonesia : An Error Correction Model Approach - Nur Bidayah (UPT Penerbitan Universitas Jember, 2020)
Liberation and globalization are the beginning of a country's economic openness. With open finance, the flow of goods and services between countries has become easier. The exchange rate is an important indicator aspect in a country's finances, where most countries in the world are currently involved in global markets. Macroeconomic shocks are indicative of shocks in external estimates. One indicator variable that is vulnerable is the exchange rate. This study aims to look at the effect of the short-term and long-term variable interest rates, inflation and the composite stock price index on the exchange rate in Indonesia. This study uses an Error Correction Model (ECM) analysis with time series data from 2009M1-2018M12. The analysis shows that in the long run, variable interest rates, inflation, and the composite stock price index have a positive effect on the exchange rate in Indonesia. The results of the analysis in the short term, interest rates and inflation variables negatively affect the exchange rate in Indonesia. While the composite stock price index variable in the long run has a positive effect on the exchange rate in Indonesia. Keywords: Exchange rates, interest rates, inflation, CSPI, Error Correction Model